Long-term outcomes and toxicity of radiotherapy for WHO Grade II and III meningiomas: a retrospective analysis of 98 patients - Tas, Kerem Tuna; Höft, Finja Svende; Agolli, Linda; Mohamed, Tasneim Abdelrahman; Sheikhzadeh, Fatima Frosan; Lishewski, Philipp; Schymalla, Markus; Zink, Klemens; Vorwerk, Hilke; Harrabi, Semi B.; Habermehl, Daniel; Adeberg, Sebastian; et al. (Journal of neuro-oncology, 2025)
Background: This retrospective study evaluated outcomes and toxicity in patients with WHO Grade II and III meningiomas treated with modern photon or particle radiotherapy, with emphasis on skull base versus non-skull base tumors. Methods: Ninety-seven patients received photon (58.2%) or particle therapy (41.8%). Median age was 61 years (range, 15–88). Tumor location was non-skull base in 69.1% and skull base in 30.9%. All patients underwent fractionated radiotherapy with a median dose of 59.4 Gy (range, 34–68). Follow-up included MRI and assessment of local control (LC), progression-free survival (PFS), overall survival (OS), and toxicity (CTCAE v5). Results: At last follow-up, 94 patients (96.9%) were alive. Median OS was not reached, with survival rates of 100% at 2 and 5 years and 99% at 8 years. Median PFS was 32.0 months, with 2- and 5-year rates of 88.7% and 66.0%. Median LC was 33.0 months, with 2- and 5-year rates of 91.8% and 72.2%. Disease progression occurred in 40 patients (41.2%), including 30 in-field and 22 outside the irradiated volume. Early toxicities were mainly Grade I–II, most commonly alopecia, fatigue, and headache. Late toxicities were less frequent, including headache, seizures, vertigo, and radiation-induced cerebral contrast enhancement (RICE). Severe late toxicity (Grade III) was rare (n = 3). Particle therapy was associated with lower rates of vertigo and headache. Conclusion: High-precision photon and particle radiotherapy achieved effective long-term control with favorable safety in high-grade meningiomas. Most adverse effects were mild and manageable, supporting the role of particle therapy in reducing selected late toxicities.